Filter for TV and video cameras - Berezhinsky, L.I.; Dae-Yong Park; Chang-Min Sung; Kwang-Ho Kwon; Sang-Hoon Chai (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
An infrared-cut filter for TV and video cameras was calculated and fabricated. The filter contains 28 alternating SiO₂ and TiO₂ layers. The filter was calculated using the principle of unequal-thickness layers. This filter has a transmittance of 95 % in 400 to 650 nm range and 1 % in 700 to1150 nm range.